PENGGUNAAN METODE KONTRASEPSI SUNTIKAN DMPA BERHUBUNGAN DENGAN DISFUNGSI SEKSUAL WANITA PADA AKSEPTOR KB SUNTIK - Jomima Batlajery; Hamidah Hamidah; Mardiana Mardiana (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
The use of hormonal contraception is a popular form of contraception in the community.This study aimed to determine the relationship between the use of DMPA injection contraceptivemethod and sexual dysfunction among injections acceptors.The method of this study is across sectional with univariate, bivariate and multivariate analisys. The sample was 104syringe family planning acceptors who meet the inclusion criteria. The results shows thatthere are 49 mothers apply DMPA method and 55 mothers remain use other method.Asmany as 55.8% of women have applied family planning program ? 24 months, 50% ofmothers are multiparous ,and 50% others are primiparous. 57 respondents are aged 20-30 years. The use of DMPA method among total 104 respondents is 48.1%,, and there are32 women experience sexual dysfunction or sexual disorders. The results of statistical testsshows that age and the duration of contraception use ? 24 months is associated with sexualdysfunction in women. Types of contraception, contraception history used before and paritywas not associated with sexual dysfunction.The conclusion of this study is that there is theinfluence between length of the use of contraception and maternal age on the incidence ofsexual dysfunction. The longer mothers use DMPA contraception, the higher their risk ofsexual dysfunction.